An integrated approach to improve effectiveness of industrial multi-factor statistical investigations - Miroshnichenko, V. I.; Simkin, O. I.; Сімкін, О. І.; Мірошниченко, В. І. (CEUR Workshop Proceedings, 2020)
An approach was developed for computer statistical analysis of big, multi-dimensional arrays of technology parameters and industrial product qual-ity indexes. It provides fully objective, mathematically comprehensive, scien-tifically grounded and physically interpretable description of the manufacturing factor effects on the performance of an industrial product. The approach inte-grates a basic Data Mining exploratory technique, multiple regression models construction and Monte-Carlo simulations. The approach was applied to indus-trial statistical arrays investigations for the ASTM A514 steel. The results ob-tained are in a good accordance with the known Material Science data and were confirmed in industry
Keywords: multi-dimensional data; exploratory technique; multiple regression models; Monte-Carlo simulations